Ekonomické a finanční dopady pandemie COVID-19 v konkrétním podniku - Březinová, Barbora (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Bakalářská práce se věnuje vyhodnocení ekonomické situace u společnosti s ručením omezeným, která si přeje zůstat v anonymitě v letech 2018-2022, kdy je v tomto období zahrnuta i problematika pandemie COVID-19. První část práce charakterizuje pojmy důležité k danému tématu, kterou se samotná práce zabývá. Druhá část je věnována výpočtu a vyhodnocení samotných ukazatelů pomocí metod uvedených v teoretické části. Poslední část práce je založena na základě výsledků analytické části a její součástí je návrh opatření, které by vedlo k zlepšení aktuální finanční situace.

The bachelor's thesis is devoted to the evaluation of the economic situation in a limited liability company that wishes to remain anonymous in the years 2018-2022, when the issue of the COVID-19 pandemic is also included in this period. The first part of the work characterizes the important terms for the given topic, which the work itself deals with. The second part is devoted to the calculation and evaluation of the indicators themselves using the methods mentioned in the theoretical part. The last part of the work is based on the results of the analytical part and part of it is a proposal for measures that would lead to an improvement in the current financial situation.
Economic and financial impact of the COVID-19 pandemic in a specific company
Keywords: COVID-19; finanční analýza; rozvaha; výkaz zisku a ztrát; quicktest; Index IN05; poměrové ukazatele; likvidita; zadluženost; Česká republika; COVID-19; financial analysis; balance sheet; profit and loss statement; quicktest; index IN05; ration indicators; liquidity; debt ratio; The Czech Republic